A construção da narração do nacional no cinema brasileiro e argentino (1995-2002) - Eduardo Dias Fonseca (2019)
The proposal of this thesis is to study the intercessions between fiction films and nationhood narration taking into account the existing relations between cinema and society. Cinema is understood as an art that is related to mass communication. There are two primordial cutouts for thinking about the construction of the nationhood narration. The first is territorial and the second is a temporal. The focus is on Brazilian and Argentinean cinematography during the period from 1995 to 2002. During the 1990s, the two territories were crossed by a series of political and economic lines that reconfigure the cinematographic making, both in film narratives and aesthetics, as well as in the institutional forms. Based on this perspective arises our questioning: what are the ways of nationhood narration that emerge from a group of films in the mentioned period? Beginning with the debate around a diversity of concepts to circumscribe the parameters of nationhood narration such as identity, representation, people, nation and national culture this research focuses on relations between the cinema, seen as a symptom to identify the marks of speeches of the national, and the construction of the nationhood narration. The films analyzed are: Carlota Joaquina, a princesa do Brazil (Brasil, 1995), directed by Carla Camuratti; Pizza, birra, faso (Argentina, 1998), directed by Bruno Stagnaro and Israel Adrián Caetano; Central do Brasil (Brasil, 1998), directed by Walter Salles; Garage Olimpo (Argentina, 1999), directed by Marco Bechis; Cronicamente inviável (Brasil, 1999), directed by Sergio Bianchi; Nueve reinas (Argentina, 2000), directed by Fabian Bielinsky; El bonaerense (Argentina, 2002), directed by Pablo Trapero; Cidade de Deus (Brasil, 2002), directed by Fernando Meirelles e Katia Lund. This thesis focuses both on the filmic text as a source for the analysis of national and on institutions and legislations for the promotion of cinema as possible ways of maintaining national discourse.